Composition for antibacterial nanogel, antibacterial nanogel prepared from composition and application of antibacterial nanogel

By using antibacterial nanogels combined with sodium alginate with carboxymethyl chitosan and manganese copper oxide nanomaterials, the problems of low antibacterial efficiency and great toxicity in the prior art are solved, and the effect of efficient antibacterial and promoting wound healing is achieved.

CN119701073APending Publication Date: 2025-03-28FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311497060.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2023-11-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing antibacterial and wound repair technologies have problems such as low efficiency, high toxicity, complex preparation and antibacterial resistance, making it difficult to effectively control bacterial spread and promote wound healing.

Method used

Carboxymethyl chitosan and manganese oxide copper nanomaterials are used as antibacterial agents, combined with sodium alginate to form an antibacterial nanogel, which effectively inhibits bacteria and promotes wound healing through physical and chemical effects.

Benefits of technology

It has achieved efficient antibacterial and promotes wound healing, has broad-spectrum bactericidal properties, low toxic side effects, and is simple and easy to perform preparation technology, and is suitable for wounds infected by drug-resistant strains.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701073A_ABST
    Figure CN119701073A_ABST
Patent Text Reader

Abstract

The invention discloses a composition for antibacterial nanogel, the antibacterial nanogel prepared from the composition and application of the antibacterial nanogel. The composition for the antibacterial nanogel is prepared from carboxymethyl chitosan, a copper manganese oxide nanomaterial, sodium alginate and water. Wherein the mass ratio of the carboxymethyl chitosan to the copper manganese oxide nano material to the sodium alginate is (1-5): (0.05-0.2): (1-5). According to the antibacterial nanogel, carboxymethyl chitosan and a copper manganese oxide nano material with high bacterial cell membrane adhesion capacity are adopted as antibacterial agents, natural gel sodium alginate is combined, no medicine component is added, and the problems of any toxic and side effects, generation of drug-resistant bacteria and the like do not exist.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to a prior application with patent application number 2023112522088 filed with the State Intellectual Property Office of China on September 26, 2023, entitled “A composition for antibacterial nanogel, antibacterial nanogel prepared therefrom and its application”. The entire text of the prior application is incorporated into this application by reference. Technical Field

[0002] The invention relates to the field of nano antibacterial technology and infected wound treatment, and in particular to a composition for antibacterial nano gel and the antibacterial nano gel prepared therefrom and its application. Background Art

[0003] The most important goal of treating skin wounds is to improve the antibacterial efficiency of wounds and the healing speed of wounds. Among them, bacterial inhibition is the main cause of harm to public health. How to effectively control and prevent the spread of bacteria is an important topic that has attracted much attention. Therefore, antimicrobial agents have a broad application market in the biomedical field. Antibiotics are mainly used to treat various bacterial infections or diseases infected by pathogenic microorganisms. The effect is more significant in the early stage of application. However, with the long-term and widespread use of antibiotics, bacterial resistance has become stronger and stronger, and microbial infection diseases have seriously threatened human health and safety.

[0004] With the development of nanotechnology and nanobiomedicine, new long-term ways to control microbial infections are gradually taking shape. Applying nanotechnology to the antibacterial field and combining it with gel can better act on the human body. The main ways in which nanomaterials inactivate bacteria are: nanomaterials efficiently adhere to cell membranes and destroy cell membranes through physical action; nanomaterials release metal ions to destroy bacterial proteins or DNA; and the production of reactive oxygen destroys lipids and DNA. At the same time, nanomaterials have the characteristic of not being limited by bacterial resistance. However, nanomaterials have certain toxicity, and excessive use will remain in the body. At the same time, nanomaterials are complex to prepare and are limited by the biofilm microenvironment, so their antibacterial efficiency is low.

[0005] Some high molecular materials, such as chitosan, polyarginine such as pyrrolidinolide, and some peptides, such as polyarginine, also have high antibacterial and wound healing properties. However, the application of cationic materials in the field of wound healing is greatly limited by the complicated steps of cationic construction, poor water solubility, and high price of peptides.

[0006] The process of wound healing mainly refers to a slow dynamic process of interaction between cells, cytoplasm and soluble media. In clinical practice, commonly used medical dressings can effectively promote healing on wounds. However, traditional dressings have the disadvantages of long wound healing time, low healing efficiency, weak hemostasis, easy infection, and long-term wound adhesion leading to secondary damage, which makes people constantly modify traditional dressings. As a kind of dressing, hydrogel can continuously absorb wound exudate, keep wounds moist, clean wounds and accelerate wound healing, so it is favored by people. However, on the one hand, as a carrier, the current gel formation rate is low, the porosity is small, the mechanical properties are poor, and it does not have the ability to load and release drugs. How to ensure the superior performance of hydrogel itself, realize the loading of drugs through additives, and realize the efficient antibacterial and repair performance of wounds is the main technical difficulty currently faced. In addition, metal ions, such as Cu, Mn, etc., have the performance of repairing wounds, especially manganese copper oxide has a good application prospect in the healing of infected wounds. How to combine it with hydrogel to achieve release is another problem to be solved. Summary of the invention

[0007] In view of the above-mentioned problems, the present invention aims to solve the shortcomings of existing antibacterial and wound repair technologies, and provides an antibacterial nanogel composition and an antibacterial nanogel prepared therefrom and its application. The antibacterial nanogel of the present invention selects carboxymethyl chitosan and manganese copper oxide nanomaterials as antibacterial agents, adds sodium alginate, and forms an antibacterial nanogel, which plays a role in high-efficiency antibacterial and promoting wound healing.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A composition for antibacterial nanogel, comprising carboxymethyl chitosan, manganese copper oxide nanomaterial, sodium alginate and water;

[0010] Wherein, the mass ratio of carboxymethyl chitosan, manganese copper oxide nanomaterial and sodium alginate is (1-5):(0.05-0.2):(1-5).

[0011] According to an embodiment of the present invention, the composition further comprises a crosslinking agent, wherein the crosslinking agent is a crosslinking agent that provides Gd 3+ , Al 3 + , Fe 3+ , Ca 2+ A compound of one or more ions, such as at least one of calcium chloride, ferric chloride, gadolinium chloride or aluminum chloride.

[0012] Preferably, the mass ratio of the cross-linking agent to carboxymethyl chitosan is 1-8:1, and exemplarily is 2.67:1.

[0013] According to an embodiment of the present invention, the manganese copper oxide nanomaterial may be one of manganese copper oxide nanosheets, manganese copper oxide nanospheres and manganese copper oxide nanorods.

[0014] According to an embodiment of the present invention, the size of the manganese copper oxide nanosheets is 100-500 nm, the size of the manganese copper oxide nanospheres is 10-200 nm, and the size of the manganese copper oxide nanorods is 100-1000 nm.

[0015] According to an embodiment of the present invention, the concentration of the manganese copper oxide nanomaterial in water is 50 to 200 μg / mL, preferably 60 to 150 μg / mL.

[0016] According to an embodiment of the present invention, the mass volume percentage of the carboxymethyl chitosan in water is 1-5% w / v, for example, 1% w / v, 2% w / v, 3% w / v, 4% w / v or 5% w / v.

[0017] According to an embodiment of the present invention, the mass percentage of sodium alginate in water is 1-5% w / v, for example, 1% w / v, 2% w / v, 3% w / v, 4% w / v or 5% w / v.

[0018] An antibacterial nanogel is obtained by gelling the above-mentioned antibacterial nanogel composition.

[0019] According to an embodiment of the present invention, the nano antibacterial gel can inhibit drug-resistant S. aureus and / or E. coli wound infection.

[0020] The present invention also provides a method for preparing the antibacterial nanogel, which comprises the following steps:

[0021] (1) preparing carboxymethyl chitosan and manganese copper oxide nanomaterials respectively;

[0022] (2) Carboxymethyl chitosan, manganese copper oxide nanomaterials, sodium alginate and a cross-linking agent which is optionally added are mixed in water to prepare an antibacterial nanogel.

[0023] According to an embodiment of the present invention, in step (1), the carboxymethyl chitosan can be prepared by deacetylation and carboxymethylation of chitin.

[0024] Preferably, deacetylation may be performed first, followed by carboxymethylation; deacetylation and carboxymethylation may also be performed simultaneously.

[0025] According to an embodiment of the present invention, in step (1), the method for preparing the manganese copper oxide nanomaterial is:

[0026] CuCl2·6H2O, MnCl2·6H2O and a weak base reducing agent are mixed to prepare manganese copper oxide nanomaterials.

[0027] According to an embodiment of the present invention, in the preparation of manganese copper oxide nanomaterials, the mass ratio of CuCl2·6H2O, MnCl2·6H2O and weak base reducing agent is (1-8):1:(1-10).

[0028] According to an embodiment of the present invention, in the preparation of manganese copper oxide nanomaterials, the weak base reducing agent is selected from at least one of urotropine (hexamethylimine), paraformaldehyde, sodium carbonate and ammonia water.

[0029] According to an embodiment of the present invention, in the preparation of manganese copper oxide nanomaterials, the mixing temperature is 60-120°C, such as 60-90°C, and the mixing time is 3-120 min, preferably 5-60 min.

[0030] According to an embodiment of the present invention, step (2) is: mixing carboxymethyl chitosan, manganese copper oxide nanomaterial, sodium alginate and a cross-linking agent in water to prepare an antibacterial nanogel.

[0031] According to an embodiment of the present invention, in step (2), the concentration of the manganese copper oxide nanomaterial in water is 50 to 200 μg / mL, preferably 60 to 150 μg / mL.

[0032] According to an embodiment of the present invention, in step (2), the mass volume ratio of the carboxymethyl chitosan in water is 1 to 5% w / v.

[0033] According to an embodiment of the present invention, in step (2), the mass ratio of sodium alginate in water is 1-5% w / v.

[0034] According to the embodiment of the present invention, step (2) is specifically as follows: carboxymethyl chitosan, manganese copper oxide nanomaterial and sodium alginate are first mixed in water, and then a crosslinking agent aqueous solution is added to prepare the antibacterial nanogel.

[0035] According to an embodiment of the present invention, in step (2), the concentration of the cross-linking agent aqueous solution is 1 to 5% w / v.

[0036] According to an embodiment of the present invention, the antibacterial nanogel is stored at 0 to -10°C, for example -4°C.

[0037] As an exemplary embodiment of the present invention, the method for preparing the antibacterial nanogel specifically comprises the following steps:

[0038] Step 1: preparing an aqueous solution of manganese copper oxide nanomaterial;

[0039] 10-80 mg of CuCl2·6H2O and 1-10 mg of MnCl2·6H2O powders were mixed, and the mixture was stirred vigorously at 60°C to 120°C at a speed of 600 r / min; 10 mg to 100 mg of a weak base reducing agent was added after 30 minutes, and the mixture was heated and stirred for 5-30 minutes; the reaction was stopped, and after cooling to room temperature, the mixture was centrifuged at 10000 r / min to obtain a precipitate, and the precipitate was washed three times with anhydrous ethanol and three times with ultrapure water to obtain a manganese copper oxide nanomaterial;

[0040] Step 2: preparing an aqueous solution of carboxymethyl chitosan;

[0041] First, 4% (w / v) chitosan powder is added to a 15% (w / v) potassium hydroxide solution, and then the solution is frozen at -30°C for 6 hours, and then the undissolved chitosan is removed by filtration and centrifugation to obtain a strong alkaline solution of chitosan; then potassium hydroxide is added to the chitosan-strong alkaline solution at 0°C to make the concentration of potassium hydroxide in the system reach 41% (w / v); then, a subsequent deacetylation reaction is carried out at 100°C for 2 to 6 hours, and then chloroacetic acid is added in an amount 5 times the mass of chitosan, and then a carboxymethylation reaction is carried out in a microwave (600 to 800W) for 4 to 8 hours;

[0042] Alternatively, after the deacetylation reaction is completed, the sample is centrifuged, washed and dried, and then redispersed in 41% (w / v) potassium hydroxide, and then subsequently carboxymethylated with chloroacetic acid;

[0043] Step 3: Dissolve 0.5 mL of 1-5% w / v sodium alginate in water, add 0.5 mL of 1-5% w / v carboxymethyl chitosan aqueous solution at room temperature; add 50-200 μg / mL of manganese copper oxide solution to the system, mix until uniform, and then add 2 mL of 2% w / v cross-linking agent aqueous solution to obtain antibacterial nanogel.

[0044] The present invention also provides the use of the antibacterial nanogel in preparing antibacterial products for skin wounds.

[0045] Beneficial effects of the present invention:

[0046] (1) The antibacterial nanogel of the present invention uses carboxymethyl chitosan and manganese copper oxide nanomaterials with strong bacterial cell membrane adhesion ability as antibacterial agents, combined with natural gel sodium alginate, without adding any drug ingredients, and does not have any toxic side effects and the production of drug-resistant bacteria.

[0047] (2) The preparation process of the manganese copper oxide nanomaterial and the antibacterial nanogel of the present invention is simple and easy.

[0048] (3) The antibacterial nanogel of the present invention has a broad-spectrum bactericidal property, and has a killing rate of more than 95% against Staphylococcus aureus and Escherichia coli.

[0049] (4) The antibacterial nanogel of the present invention has an extremely low product dosage during use, which greatly improves the safety of biological organisms.

[0050] (5) The antibacterial nanogel of the present invention is easy to apply / spray on the wound in the form of a hydrogel, which greatly improves the drug administration efficiency and reduces systemic toxic side effects.

[0051] (6) The present invention uses manganese copper oxide nanomaterials and carboxymethyl chitosan for dual antibacterial effects, which can achieve low-dose, high-efficiency killing and rapid healing of wounds infected with drug-resistant strains. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 , wherein AC is the transmission electron microscopy images of the manganese copper oxide nanoparticles of Example 1 at different reaction times (5 minutes, 10 minutes and 15 minutes respectively);

[0053] DF is the transmission electron microscopy images of manganese copper oxide nanoparticles of Examples 2a-2c;

[0054] Figure 2 , wherein AD is the high-magnification transmission electron microscopy image of manganese copper oxide under the conditions of 5min, 10min and 30min in Example 1;

[0055] EH is the element distribution diagram of manganese copper oxide under 30 min conditions in Example 1;

[0056] Figure 3 : A is a schematic diagram of the step-by-step preparation of sodium alginate-carboxymethyl chitosan-manganese copper oxide nanosheet gel in the present invention;

[0057] B is a schematic diagram of wound repair in the present invention:

[0058] CD are scanning electron micrographs of the antibacterial nanogel at different magnifications in Example 3;

[0059] E is a photograph of the antibacterial nanogel in Example 3;

[0060] FH is the change in tensile stress, elongation after break and tensile modulus of different nano antibacterial gels under a certain tensile strain coefficient in Example 3 and Comparative Examples 1-2.

[0061] Figure 4 : AB are the killing effect diagrams of different volumes of antibacterial nanogels and PBS on Escherichia coli and the adhesion diagram of gel to Escherichia coli in Application Example 1;

[0062] CD is the killing effect of different volumes of antibacterial nanogel and PBS on Staphylococcus aureus and the adhesion of gel to Staphylococcus aureus in Application Example 1;

[0063] E is a transmission electron microscopic image of the killing of drug-resistant Staphylococcus aureus by PBS in Application Example 1, carboxymethyl chitosan-sodium alginate solution (HCCA) in Comparative Example 1, and sodium alginate-carboxymethyl chitosan-copper manganese oxide nanosheets (HCCA-Cu / Mn) nanogel in Example 3;

[0064] Figure 5 AB is the regional trace diagram of the effects of the antibacterial nanogel in Example 3, the sodium alginate-copper manganese oxide nanogel (HA-Cu / Mn) in Comparative Example 2, and the sodium alginate nanogel (HA) in Comparative Example 3 on the healing and closure of infected wounds in living bodies in Application Example 2

[0065] C is a graph showing the wound healing efficiency of the antibacterial nanogel in Application Example 2, Example 3 and Comparative Examples 2 and 3;

[0066] D is the weight change of mice in different groups in Application Example 2;

[0067] E is the antibacterial efficiency of the antibacterial nanogel in Application Example 2, Example 3 and Comparative Examples 2 and 3;

[0068] FI graphs are the Guisam staining, H&E staining, CD36+ positive immunostaining and Mason staining of the mouse wounds after 12 days of treatment with the antibacterial nanogel in Application Example 2, Example 3 and Comparative Examples 2 and 3.

[0069] Among them, "CMC" is carboxymethyl chitosan; "Alg" is sodium alginate; "HCCA-Cu / Mn" is Example 3, sodium alginate-carboxymethyl chitosan-manganese copper oxide antibacterial nano gel; "HA-Cu / Mn" is Comparative Example 2, sodium alginate-manganese copper nano gel; "HA" is Comparative Example 3, sodium alginate gel. DETAILED DESCRIPTION

[0070] The technical scheme of the present invention will be described in more detail according to the embodiments of the present invention in conjunction with specific examples. It should be understood that the following examples are only exemplary illustrations and explanations of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0071] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0072] Example 1

[0073] The preparation of manganese copper oxide nanoparticles includes the following steps:

[0074] First, 60 mL of ultrapure water was placed in a round-bottom flask and heated in a 90 °C oil bath for 30 min. Then, 75 mg of CuCl2·6H2O and 7.5 mg of MnCl2·6H2O powder were added to the reaction system and vigorously stirred at 600 r / min for 30 min.

[0075] Then, 1 mmol of hexamethylenetetramine (hexamethyldisilamine) was added, and the reaction was continued for 30 minutes with heating and stirring. After the reaction was stopped and cooled to room temperature, the precipitate was centrifuged at 10,000 r / min and washed three times with anhydrous ethanol and ultrapure water to obtain manganese copper oxide nanoparticles. The products at 5 minutes, 15 minutes and 30 minutes of reaction were respectively taken for transmission electron microscopy test.

[0076] Figure 1 AC are transmission electron micrographs of manganese copper oxide nanoparticles prepared at different reaction times (5 min, 10 min and 15 min, respectively).

[0077] from Figure 1 It can be seen from Figures AC that the particle size of manganese copper oxide nanoparticles increases with time and reaches a maximum value of 200 nm at 30 min.

[0078] Examples 2a-2c

[0079] The difference between Example 2a-2c and Example 1 is that the hexamethylimide in Example 1 is replaced by polyformaldehyde, sodium carbonate and ammonia water, respectively, and manganese copper oxide nanoparticles are prepared after 30 minutes.

[0080] Figure 1 DF is a transmission electron microscope image of manganese copper oxide nanoparticles in Examples 2a-2c of the present invention;

[0081] from Figure 1 As can be seen from DF, the morphologies of manganese copper oxide nanoparticles are nanosheets, nanospheres, and nanorods, respectively.

[0082] 300 μg of the manganese copper oxide nanosheets prepared in Example 1 under the conditions of 5 min, 10 min and 30 min were respectively dissolved in 1 mL of ultrapure water, and 10 μl of the solution was dripped on the ultrathin carbon film and dried in an oven at 40° C. The morphology, size and dispersibility of the samples were observed using a high-resolution transmission electron microscope / high-resolution scanning transmission electron microscope with a voltage of 100 kV, and a clear and pollution-free field of view was selected for photographing and preservation.

[0083] Figure 2 AD is the high-resolution transmission electron microscopy of the manganese copper oxide nanosheets in Example 1 at 5 min, 10 min and 30 min. Figure 2As shown in the electron microscope images of AD, the nanoparticles have relatively uniform particle size and good dispersion under the electron microscope; among them, the sizes of manganese copper oxide nanosheets are 100nm (A), 150nm (B), and 200nm (C, D).

[0084] Manganese copper oxide nanosheets with a particle size of 200 nm were selected for component analysis based on the characteristic energy of X-ray photons of different elements. The specific steps are as follows:

[0085] 300 μg of the manganese copper oxide nanosheets with a particle size of 200 nm obtained by reacting for 30 min in Example 1 were dissolved in 1 mL of ultrapure water, 10 μl of the solution was dripped onto the ultrathin carbon film, and dried in an oven at 40°C. The morphology, size, and dispersion of the sample were observed and analyzed using an energy spectrometer at a voltage of 200 kV. The test results are shown in FIG. Figure 2 As shown in EH, Figure 2 H is the superposition diagram of three elements; Figure 2 From the electron microscope photo of EH, it can be seen that the main elements of 200nm manganese copper oxide nanosheets are Cu( Figure 2 E), Mn( Figure 2 F) and O( Figure 2 G).

[0086] Example 3

[0087] The preparation method of sodium alginate-carboxymethyl chitosan-manganese copper oxide nano antibacterial gel (referred to as HCCA-Cu / Mn) comprises the following steps:

[0088] Preparation of carboxymethyl chitosan: First, add 4% (w / v) chitosan powder to 15% (w / v) potassium hydroxide solution, freeze at -30°C for 6h, and then remove the undissolved chitosan by filtration and centrifugation to obtain a strong alkaline solution of chitosan. Then, potassium hydroxide is added to the chitosan-strong alkaline solution at 0°C until the concentration of potassium hydroxide in the system reaches 41% (w / v). Then, a subsequent deacetylation reaction is carried out at 100°C for 4h, and then chloroacetic acid with a mass of 5 times that of chitosan is added to the reaction system, and the above reaction solution is placed in a microwave (700W) for a subsequent carboxymethylation reaction for 6h. Finally, add ultrapure water with a volume twice that of the reaction solution to the sample, adjust the pH to 7.0 with glacial acetic acid, filter it through a Buchner funnel, centrifuge it with ultrapure water, and then use anhydrous ethanol to wash and replace the water molecules in the sample. The obtained carboxymethyl chitosan sample is dried in an oven at 65°C overnight and kept for subsequent use.

[0089] Figure 3 A is a schematic diagram of the step-by-step preparation of sodium alginate-carboxymethyl chitosan-manganese copper oxide nanosheet gel in the present invention.

[0090] The preparation process of the antibacterial nanogel is as follows: 0.5 mL of 3% w / v sodium alginate is dissolved in water, and 0.5 mL of 3% w / v carboxymethyl chitosan is added at room temperature. 0.1 mL of 100 μg / mL manganese copper oxide nanomaterial prepared in Example 1 under 30 min is added to the system, mixed until uniform, and then 2 mL of 2% w / v calcium chloride aqueous solution is added to obtain the antibacterial nanohydrogel.

[0091] Figure 3 B is a schematic diagram of wound repair in the present invention: bacterial infection wound, sodium alginate-carboxymethyl chitosan-copper manganese oxide nanosheet antibacterial and tissue repair wound, and finally repaired wound healing.

[0092] Characterization of sodium alginate-carboxymethyl chitosan-manganese copper oxide nano-antibacterial gel: The gel was prepared into cubes with a size of 20 mm × 20 mm × 20 mm, and its tensile strain coefficient, elongation at break and tensile modulus were measured using a hydrogel tensile testing machine (CMT6103, MST, USA) and a modulus meter (TJFH-EVD, China).

[0093] Figure 3 C and 3D are scanning electron micrographs of the antibacterial nanogel at different magnifications in Example 3. Figure 3 The scanning electron microscopy results of C and 3D showed that the antibacterial nanogel was successfully prepared.

[0094] Comparative Example 1

[0095] The difference between Comparative Example 1 and Example 3 is that in the preparation of the antibacterial nanogel, no manganese copper oxide nanoparticles were added, and the content of manganese copper oxide nanoparticles in Example 1 was replaced by carboxymethyl chitosan in equal proportion, and the prepared antibacterial nanogel was recorded as sodium alginate-carboxymethyl chitosan gel.

[0096] Figure 3 E is a photo of the antibacterial nanogel of Example 3 and Comparative Example 1. Figure 3 E It can be seen that manganese copper oxide nanoparticles can be uniformly dispersed in the gel (such as Figure 3 E right).

[0097] Comparative Example 2

[0098] The difference between Comparative Example 2 and Example 3 is that in the preparation of the antibacterial nanogel, carboxymethyl chitosan was not added, and the content of carboxymethyl chitosan in Example 1 was replaced by manganese copper oxide in equal proportion, and the prepared antibacterial nanogel was recorded as sodium alginate-manganese copper nanogel.

[0099] Comparative Example 3

[0100] The difference between Comparative Example 3 and Example 3 is that carboxymethyl chitosan and manganese copper oxide were not added in the preparation of the antibacterial nanogel, and the contents of carboxymethyl chitosan and manganese copper oxide in Example 1 were replaced by sodium alginate in equal proportions, and the prepared antibacterial nanogel was recorded as HA.

[0101] Figure 3 FH are respectively the tensile stress change, elongation after break and tensile modulus of different nano antibacterial gels in Example 3 of the present invention and Comparative Examples 1-2 under a certain tensile strain coefficient. Figure 3 It can be seen from FH that compared with Comparative Examples 1 and 2, the tensile stress of the antibacterial nanogel (HCCA-Cu / Mn) gel after adding carboxymethyl chitosan and manganese copper oxide nanoparticles increased by 31.2% and 16.7% respectively; the elongation at break increased by 25.3% and 23.1% respectively; and the tensile modulus increased by 6 times and 1 times respectively.

[0102] Application Example 1

[0103] The antibacterial nanogel in Example 3 was dissolved in water, wherein the concentration of the antibacterial nanogel was 100 μg / mL, and sterilized by high pressure at 121° C. for half an hour to obtain antibacterial nanogel aqueous solution samples of different volumes (10 μL, 50 μL, 100 μL, 150 μL, 200 μL).

[0104] The frozen stock solution of Staphylococcus aureus / Escherichia coli was dispersed in 10% glycerol and stored in a -80°C refrigerator. 10 μL of the bacterial solution was scraped onto an LB solid agarose plate (tryptone 10 g / L, yeast extract 5 g / L, sodium chloride 10 g / L, agar powder 15 g / L) using a sterile pipette tip. After being placed in a 37°C incubator for overnight culture, a single colony was picked up with a sterile pipette tip and placed in 50 mL of LB liquid culture medium (tryptone 10 g / L, yeast extract 5 g / L, sodium chloride 10 g / L), pipetted evenly, and the culture solution was placed in a 37°C shaker and shaken (300 rpm / min) overnight.

[0105] 100 μL of bacterial suspension was placed in a 96-well plate and the optical density at 600 nm was measured with an ELISA reader to determine the concentration of the bacterial suspension. The bacterial suspension was diluted step by step with physiological saline to obtain a bacterial concentration of 1×10 8 CFU / mL bacterial suspension for later use.

[0106] After the antibacterial nanogel aqueous solution sample was cooled to 35-55°C, 10 μL of PBS or different volumes (10 μL, 50 μL, 100 μL, 150 μL, 200 μL) of antibacterial nanogel aqueous solution were added to 5 mL of the bacterial suspension, and the solution was placed in a 37°C shaker and shaken (300 rpm / min) for 2 h.

[0107] Take 100 μL of the bacterial suspension on an LB solid agar plate, spread it evenly with a glass scraper, and then place the plate in a 37°C incubator for 24 h.

[0108] Figure 4 AB are the killing effect diagrams of different volumes of antibacterial nanogels and PBS on Escherichia coli and the adhesion diagram of antibacterial nanogels on Escherichia coli in Application Example 1, respectively;

[0109] Figure 4 CD are the killing effect diagrams of different volumes of antibacterial nanogels and PBS on Staphylococcus aureus in Application Example 1 and the adhesion diagram of antibacterial nanogels on Staphylococcus aureus.

[0110] The growth of the two bacteria Figure 4 As shown in A and C, it can be seen from the results that, compared with the PBS group, the antibacterial nanogel treated with the present invention has a high efficiency in killing bacteria, especially in the Staphylococcus aureus group, after being treated with 200 μL, 100 μg / mL gel aqueous solution, all the bacteria were killed, indicating that the antibacterial nanogel of the present invention has the ability to inhibit bacterial growth.

[0111] Escherichia coli and Staphylococcus aureus were frozen in 10% glycerol, respectively, in a -80 ° C refrigerator, 10 μL of bacterial solution was scraped on the LB solid agarose plate using a sterile pipette tip, and placed in a 37 ° C incubator for overnight culture to form visible colonies. Use a pipette tip to pick a single colony and LB liquid culture medium, shake overnight (37 ° C, 220rpm, 12h). Take the above 100 μL bacterial suspension and add it to 5mL LB liquid culture medium. In triplicate, add the same volume of PBS, HCCA in Comparative Example 1, and the antibacterial nanogel liquid under the conditions of 30min in Example 3, respectively, and place it in a 37 ° C shaker, shake (300rpm / min) for 6h, 12h, and 24h. Add the above-treated 1mL bacterial suspension to a 5mL centrifuge tube, centrifuge at 3000-5000rpm for 1-5min, and after obtaining the bacterial precipitate, add 5mL of physiological saline to the final centrifugal product and resuspend it for standby use. Add 4 mL of 2.5% paraformaldehyde to the bacterial sample dispersed in physiological saline, and place the sample in a 4°C refrigerator for 30 minutes. Centrifuge the sample at 3000-5000 rpm for 1-5 minutes to obtain bacterial precipitation. The final centrifugal product is dispersed with 30% ethanol-water solution, incubated for 5 minutes, and centrifuged at 3000-5000 rpm for 1-5 minutes to obtain a preliminary dehydrated bacterial sample. Then, the sample is dehydrated step by step with 40%, 50%, 60%, 70%, 80%, 90%, and 100% ethanol-water solution. The bacterial sample dispersed in anhydrous ethanol is dripped onto a silicon dioxide wafer, and the bacterial morphology is observed under 80KV by a scanning electron microscope (LEO1530VP, Germany).

[0112] like Figure 4 As shown in B and D, the manganese copper oxide in the gel has a high adhesion to both Staphylococcus aureus and Escherichia coli.

[0113] Figure 4 E is a transmission electron microscopic image of the killing of drug-resistant Staphylococcus aureus by PBS in Application Example 1, carboxymethyl chitosan-sodium alginate solution (HCCA) in Comparative Example 1, and the antibacterial nanogel in Example 3; Figure 4 E It can be seen that compared with the PBS group, the morphology of Staphylococcus aureus treated with carboxymethyl chitosan-sodium alginate (HCCA, i.e., Comparative Example 1) is distorted. The antibacterial efficiency of the antibacterial nanoparticles of the present invention is much greater than that of the carboxymethyl chitosan-sodium alginate solution, and after 24 hours of incubation, the bacteria are completely ruptured and degraded. The above results show that the antibacterial nanogels of the present invention have efficient antibacterial properties.

[0114] Application Example 2

[0115] Reference Figure 5A and 5B, To investigate the antibacterial and therapeutic effects of antimicrobial nanogels on infected wounds, a wound model was established on the right hind thigh muscle of Balb / C mice.

[0116] The specific method is as follows: clean the hair of the right hind leg of a female Balb / C mouse (19-23 g), use a skin sampler with a diameter of 2-8 mm to make a hole in the mouse skin to create a model. Use a syringe to inject 100 μL of 10 4 ~10 9 CFU / mL of Staphylococcus aureus, and apply bacterial suspension to the wound at the same time.

[0117] The mice were divided into three groups (6 mice in each group), and 24 hours after the bacterial solution was injected, 10-100 μL of HCCA-Cu / Mn in Example 3, HA-Cu / Mn in Comparative Example 2, and HA in Comparative Example 3 were sprayed on the wound. The wound healing was recorded by taking photos, and the weight of the mice was measured at the same time.

[0118] Use a cotton swab to scrape bacteria from the wounds of mice treated with different gels, place them in 5 mL of LB liquid culture medium, place the culture medium in a 37°C shaker, and shake (300 rpm / min) overnight. Take 100 μL of the above bacterial suspension on an LB solid agar plate, spread it evenly with a glass scraper, and place the above plate in a 37°C incubator for incubation for 24 hours. At the same time, set up a PBS control group, count the colonies in the plate, and calculate the antibacterial efficiency compared with the control group.

[0119] The healing rate of mouse wounds and the schematic diagram of wound healing were analyzed by Image J.

[0120] On the 12th day, the mice were killed, and the wound tissues and important organ tissues (heart, liver, spleen, lung, and kidney) were removed and placed in 4% paraformaldehyde. The wound tissues and organ tissues were then stained with H&E, and the wound tissues were stained with Masson, Giemsa, and CD36+ cell immunostaining.

[0121] Figure 5 AB is the regional trace diagram of the healing and wound closure of the living infected wound by the antibacterial nanogel (HCCA-Cu / Mn) in Example 3, HA-Cu / Mn in Comparative Example 2, and HA in Comparative Example 3 in Application Example 2. Figure 5 B and Figure 5 A one to one correspondence.

[0122] Figure 5 C is a graph showing the healing efficiency of wounds treated with the antibacterial nanogel (HCCA-Cu / Mn) in Example 3, HA-Cu / Mn in Comparative Example 2, and HA in Comparative Example 3 in Application Example 2. The healing efficiency was calculated by Image J by dividing the area of ​​the healed wound by the area of ​​the initial wound.

[0123] from Figure 5 From the wound healing photos, healing diagrams and healing efficiencies in AC, it can be seen that the antibacterial and healing efficiencies of the three gels on wounds are as follows: HCCA-Cu / Mn>HA-Cu / Mn>sodium alginate (HA) gel.

[0124] Figure 5 D is a graph showing the weight changes of mice in different groups in Application Example 2.

[0125] Figure 5 E is the antibacterial efficiency of the antibacterial nanogel (HCCA-Cu / Mn) in Example 3 and HA-Cu / Mn in Comparative Example 2 in Application Example 2.

[0126] from Figure 5 As can be seen from E, through the wound bacteria pouring plate, it can be found that the antibacterial efficiency (95%) of the carboxymethyl chitosan-sodium alginate-manganese copper oxide nanogel of Example 3 is significantly greater than that of sodium alginate and manganese copper oxide nanogel (66.4%), that is, Comparative Example 2, which can prove the important role of carboxymethyl chitosan in antibacterial gel.

[0127] Figure 5 In D, no significant changes were found in the body weights of the three mice during the treatment, which proves the biocompatibility of the antibacterial nanogel of the present invention.

[0128] Figure 5 The FI images are respectively the Guisam staining, H&E staining, CD34+ positive immunostaining and Mason staining of the wounds of different groups of mice in Application Example 2.

[0129] Figure 5 FI pathological staining shows that the carboxymethyl chitosan-sodium alginate-copper manganese oxide nanogel treatment group has the lowest bacterial residue, intact skin tissue, the largest collagen deposition, and the lowest CD36+ distribution, proving that in terms of wound healing speed, Example 3>Comparative Example 2>Comparative Example 3.

[0130] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An antibacterial nanogel composition, characterized in that: It includes carboxymethyl chitosan, manganese copper oxide nanomaterials, sodium alginate and water; Wherein, the mass ratio of carboxymethyl chitosan, manganese copper oxide nanomaterial and sodium alginate is (1-5):(0.05-0.2):(1-5).

2. The composition according to claim 1, characterized in that The composition also includes a crosslinking agent, and the crosslinking agent is a Gd 3+ , Al 3+ , Fe 3+ , Ca 2+ A compound of one or more ions, such as at least one of calcium chloride, ferric chloride, gadolinium chloride or aluminum chloride.

3. The composition according to claim 1 or 2, characterized in that The mass ratio of the cross-linking agent to carboxymethyl chitosan is 1-8:

1. Preferably, the manganese copper oxide nanomaterial is one of manganese copper oxide nanosheets, manganese copper oxide nanospheres and manganese copper oxide nanorods. Preferably, the size of the manganese copper oxide nanosheets is 100-500 nm, the size of the manganese copper oxide nanospheres is 10-200 nm, and the size of the manganese copper oxide nanorods is 100-1000 nm.

4. The composition according to any one of claims 1 to 3, characterized in that The concentration of the manganese copper oxide nanomaterial in water is 50-200 μg / mL. Preferably, the mass volume percentage of the carboxymethyl chitosan in water is 1-5% w / v. Preferably, the mass percentage of the sodium alginate in water is 1-5% w / v.

5. An antibacterial nanogel, which is obtained by gelling the composition for antibacterial nanogel according to any one of claims 1 to 4. Preferably, the nano antibacterial gel is used to inhibit drug-resistant S. aureus and / or E. coli wound infections.

6. The method for preparing the antibacterial nanogel according to claim 5, characterized in that: The method comprises the following steps: (1) preparing carboxymethyl chitosan and manganese copper oxide nanomaterials respectively; (2) Carboxymethyl chitosan, manganese copper oxide nanomaterials, sodium alginate and a cross-linking agent which is optionally added are mixed in water to prepare an antibacterial nanogel.

7. The method according to claim 6, characterized in that In step (1), the preparation method of the manganese copper oxide nanomaterial is: CuCl2·6H2O, MnCl2·6H2O and a weak base reducing agent are mixed to prepare manganese copper oxide nanomaterials. Preferably, the mass ratio of CuCl2·6H2O, MnCl2·6H2O and the weak base reducing agent is (1-8):1:(1-10). Preferably, the weak base reducing agent is selected from at least one of urotropine (hexamethylimine), paraformaldehyde, sodium carbonate and ammonia water. Preferably, in the preparation of manganese copper oxide nanomaterials, the mixing temperature is 60-120° C. and the mixing time is 3-120 min.

8. The method according to claim 6, characterized in that In step (2), the concentration of the manganese copper oxide nanomaterial in water is 50 to 200 μg / mL.

9. The method according to claim 6, characterized in that In step (2), the mass volume ratio of the carboxymethyl chitosan in water is 1-5% w / v. Preferably, in step (2), the mass ratio of sodium alginate in water is 1-5% w / v. Preferably, in step (2), the concentration of the crosslinking agent aqueous solution is 1 to 5% w / v.

10. Use of the antibacterial nanogel according to claim 5 in the preparation of antibacterial products for skin wounds.